Comparison of alkene hydrogenation in carbon nanoreactors of different diameters: probing the effects of nanoscale confinement on ruthenium nanoparticle catalysis. Issue 40 (3rd October 2017) - Aygün, Mehtap; Stoppiello, Craig T.; Lebedeva, Maria A.; Smith, Emily F.; Gimenez-Lopez, Maria del Carmen; Khlobystov, Andrei N.; Chamberlain, Thomas W.
Abstract : Exploratory, competitive hydrogenation reactions reveal the optimum level of confinement to control chemical reactions. Abstract : The catalytic properties of ruthenium nanoparticles (RuNPs) supported in carbon nanoreactors of different diameters – single walled carbon nanotubes (SWNTs, width of cavity 1.5 nm) and hollow graphitised nanofibers (GNFs, width of cavity 50–70 nm) – were evaluated using exploratory alkene hydrogenation reactions and compared to RuNPs adsorbed on the surface of SWNT or deposited on carbon black in commercially available Ru/C. Supercritical CO2 is shown to be essential to enable efficient transport of reactants to the catalytic RuNPs, particularly for the very narrow RuNP@SWNT nanoreactors. Though the RuNPs in SWNT are observed to be highly active, they simultaneously reduce the accessible volume of very narrow SWNTs by 30–40% resulting in lower overall turnover numbers (TONs). In contrast, RuNPs confined in wider GNFs were completely accessible and demonstrated remarkable activity compared to unconfined RuNPs on the outer surface of SWNTs or carbon black. Control of the nanoscale environment around the catalytic RuNPs significantly enhances the stability of the catalyst and influences the local concentration of reactant molecules in close proximity to the RuNPs, illustrating the comparable importance of confinement to that of metal loading and size of NPs in the catalyst. Interestingly, extreme spatial confinement also appeared not to be the best strategy for controlling the selectivity of hydrogenations in a competitive reaction of norbornene and benzonorbornadiene, with wider RuNP@GNF nanoreactors displaying enhanced selectivity for the hydrogenation of the aromatic group containing alkene (benzonorbornadiene). This is attributed to the presence of nanoscale graphitic step-edges within the GNF making them an attractive alternative to the extremely narrow SWNT nanoreactors for preparative catalysis.